(untitled) (REMUNOM, 2026)
This paper presents an in-depth analysis of the educational rigidity associated with the parenting model known as "tiger mothers," examining its implications considering human dignity and the universal rights of the child. The research adopts a qualitative approach, exploratory and analytical-interpretative in nature, based on a systematic literature review and documentary analysis of international normative instruments. The theoretical framework articulates the critique of the performance society, developed by Byung-Chul Han (2019), with the cultural approach to high educational performance present in Amy Chua (2012), establishing a dialogue with the Universal Declaration of Human Rights and the Convention on the Rights of the Child. Methodologically, a comparative historical-social analysis is conducted between contexts in East Asia and the Brazilian scenario, investigating how economic, cultural, and structural factors influence the early internalization of the productivist logic. It argues that the excessive pursuit of academic excellence, although frequently legitimized as an instrument of social mobility, can result in practices that are potentially harmful to the integral development of children and adolescents. It is concluded that the normalization of high performance in childhood requires critical review from a human rights perspective, especially regarding the ethical and legal limits of performance demands in the family and educational environment.